The molecular basis for the recognition of misfolded glycoproteins by the UDP-Glc:glycoprotein glucosyltransferase. - Sousa, M (1995)
The UDP-Glc:glycoprotein glucosyltransferase is a soluble enzyme of the endoplasmic reticulum that glucosylates protein-linked Man7-9GlcNAc2 to form the monoglucosylated derivatives. In vivo the reaction products are immediately deglucosylated by glucosidase II. The glucosyltransferase has a unique property: it glucosylates misfolded, but not native, glycoproteins. It has been proposed that the glucosyltransferase participates, together with calnexin, in the control mechanism by which only properly folded glycoproteins can exit from the endoplasmic reticulum. In this paper it is demonstrated that the glucosyltransferase recognizes two elements in the acceptor substrates: the innermost N-acetylglucosamine unit of the oligosaccharide and protein domains exposed in denatured, but not in native, conformations. Both determinants have to be covalently linked. In many cases the first element is not accessible to macromolecular probes in native conformations. Concerning the protein domains, it is demonstrated here that the glucosyltransferase interacts with hydrophobic amino acids exposed in denatured conformations. More disordered conformations, i.e. those exposing more hydrophobic amino acids, were found to be those having higher glucose acceptor capacity. It is suggested that both accessibility of the innermost N-acetylglucosamine unit and binding to hydrophobic patches determine the exclusive glucosylation of misfolded conformations by the glucosyltransferase.